PROFIL PNEUMONIA PADA PASIEN RAWAT INAP PARU RSUP M. DJAMIL - Nilas Warlem; Abdullah, Dessy; Elfahmi; Soufni Morawati; Yanti Fitri Yasa; Jenny Tri yuspitasari; Rifaldo Yudistira (Nusantara Hasana Journal, 2024)
Pneumonia is an inflammation that affects the lung parenchyma, which can be caused by microorganisms, aspiration of gastric juices, foreign bodies and hypersensitivity reactions. The crude fatality rate (CFR) of pneumonia was quite high, namely 7.6%. In 2013, pneumonia increased was found 5878 cases with a prevalence of 3.1% in West Sumatra. Objective of this research to determine the profile of pneumonia in lung patients RSUP M. Djamil Padang. The type and design of this study is a retrospective observational descriptive study. This study using 54 samples with simple random sampling technique. Univariate data analysis and data processing using the computerized SPSS program version 25.0. Most of the patients with pneumonia were 56-65 years old, namely 17 people (32.7%), the most gender was male, namely 27 people (51.9%), the most occupation was IRT, namely 21 people (40.4 %), the most comorbidities were absent, namely 16 people (30.8%), the highest levels of leukocytes were abnormal, namely 45 people (86.5%), the most used drugs were the kinolone group, namely 34 people (65.4 %), the most germs were chlamydia pneumonia, namely 29 people (55.8%), the most length of treatment was daily, namely 34 people (65.4%). Most age is 56-65 years old, most sex is male, most occupation is IRT, most comorbidities are absent, most leukocyte levels are abnormal, most drugs used are kinolones, most bacteria are Chlamydia pneumonia , the most length of treatment is daily.